Agglomeration and regional imbalance: Why? And is it bad? - Jacques-François Thisse (EIB Papers, 2000)
In a world of globalisation, it is tempting to foresee the 'death of distance' and, once the impediments to mobility have declined sufficiently, to wait for the predictions of the neo-classical theory of factor mobility to materialise. According to this theory, production factors respond to market disequilibrium by moving from regions in which they are abundant toward regions in which they are scarce. In equilibrium the capital-labour ratio is equal across regions, thus implying that both factors receive the same return in each region. In other words, the mobility of production factors would guarantee the equalisation of their returns across regions. As a consequence, there would be no reasons anymore to worry about where activities locate.
Keywords: 330; Agglomerationseffekt; Regionale Disparität; Peripheres Gebiet; Theorie